Evaluation of the Satisfaction of Users of Weather Forecast Systems with the Service Quality Method - Rianti, Eva; Rizky, Syafrika Deni; Nugraha, Fariz Haris (Sinkron : Jurnal dan Penelitian Teknik Informatika, 2020)
This research was conducted to test the user's satisfaction of the weather forecast system that had been previously applied to the Teluk Bayur BMKG. The weather forecasting service at the Padang Bayur Padang BMKG has basically fulfilled the objectives of the company. However, over time, evaluation is needed so that the effectiveness of the use of the system can be known, so the system can continue to be developed. To overcome these problems, it is necessary to evaluate the performance of the system. One way is to measure user satisfaction by using Service Quality. This method is one of the techniques used to measure the level of user satisfaction with the system. Based on the results of the measurement of the quality of the weather forecast system, the results are obtained that the system user is satisfied with the system performance, but there are several indicators on the system whose performance is not fully maximized, so that there needs to be improvements and improvements of the system performance.